KELAYAKAN SISTEM INTEGRASI SAPI DENGAN PERKEBUNAN KELAPA SAWIT DI PROPINSI SUMATERA SELATAN - Yamin, M.; Muhakka, Muhakka; Abrar, A. (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2010)
Cattle population and its growth in south sumatera province was far away from it should be. Therefore, efforts to improve and increase cattle population in south sumatera is an emerged. However, south sumatera has voluminous palm coconut plantation where stem and midrib fruit brunch, empty palm brunch is unused by product of plantation. They can be used as feed for cattle. Besides, palm coconut area and its inter tree forages can be used as exercise area for cattle and feed. SISKA model in south sumatera were define as fattening model, breeding model and combination model. These models were done by plasma farmer with group management working for fattening model, individiual management working for breeding and combination model. The goal of this study was to study feasibility model of fattening and breeding mainly in plasma farmer level. Descriptive analysis method were used to determined feasibility model. Financial aspects was determined using feasibility parameters as Benefit Cost Ratio (B/C Ratio), Net Present Value (NPV) dan Internal Rate of Return (IRR). The results shows that : NPV Rp.28,3 millions for fattening; Rp.112,2 millions for breeding and Rp. 37,7 millions for combination model; BC ratio for fattening, breeding and combination models were 1,35;2,30;1,50 respectively and IRR percentage for fattening, breeding and combination models were 20;32;16 respectively